Lifestyle Challenges: The Impact of Eating Habits and Disorders on Individuals and Society - Gautam, Shaurya (Journal of Advanced Research in HR and Organizational Management, 2023)
In our contemporary world, the pervasive influence of marketing and relentless advertising has given rise to a culture of excessive consumption, turning individuals into compulsive eaters enticed by the allure of advertised products. This phenomenon not only poses risks to individual consumers but also has broader implications for society. Marketers and advertisers must recognize that the ultimate goal of companies should extend beyond mere sales to enhancing people’s well-being. This extended exploration dissects the intricate connections between marketing strategies, consumer choices, and the resultant impact on mental and physical well-being, particularly in the context of lifestyle challenges related to eating habits and disorders. The dark side of consumption is unveiled as enticing promotions and clever advertising campaigns fuel a culture of excess and contribute to the proliferation of unhealthy eating habits. Beyond immediate health risks, this darker aspect casts a shadow over societal well-being, prompting ethical questions about the responsibility of companies in shaping public health. Aligning with nutritional needs and following time-tested eating intervals creates a harmonious relationship with food, resisting the temptation of taste and fashion. Guidelines for healthy eating encompass consuming food at proper intervals, resisting taste temptations, understanding one’s body, and minimizing food wastage through awareness. Educational initiatives play a pivotal role in raising awareness about scientific eating practices, emphasizing a holistic approach to nutrition, and fostering a culture of mindful eating. Educational initiatives must go beyond conventional teachings, incorporating practical experiences, interactive workshops, and community involvement. Leveraging digital platforms enhances accessibility, and workplace wellness programs extend the reach of educational efforts. A comprehensive and dynamic approach to education empowers individuals to make conscious and health-conscious choices, contributing to a society that prioritizes well-being and sustains positive lifestyle practices for generations to come.